2009
DOI: 10.1007/s10067-009-1285-x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and referral of rheumatoid arthritis by primary care physician: results of a pilot study on the city of Pisa, Italy

Abstract: The aims of the present study were to evaluate, in the city of Pisa: (1) the prevalence of rheumatoid arthritis; (2) the reliability of the prevalence estimated by primary care physicians, using the rheumatologist's diagnosis as the "gold standard" and (3) the economic impact of the disease. The Tuscany registry of primary care physicians constituted the framework from which a sample of subjects was selected. The rheumatoid arthritis (RA) subjects >18 years followed by each primary care physician constituted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…Recent Italian population data have shown that the prevalence of RA has increased to 0.49% [7], in line with the findings of epidemiological studies carried out in the United State (US) [8]. The incidence of new cases is increasing [9], but it has not been followed by an increase in the use of biological therapy, which was prescribed for only 6.3% of RA patients in 2009 [10].…”
Section: Introductionmentioning
confidence: 66%
“…Recent Italian population data have shown that the prevalence of RA has increased to 0.49% [7], in line with the findings of epidemiological studies carried out in the United State (US) [8]. The incidence of new cases is increasing [9], but it has not been followed by an increase in the use of biological therapy, which was prescribed for only 6.3% of RA patients in 2009 [10].…”
Section: Introductionmentioning
confidence: 66%
“…Three studies conducted population‐based surveys to define cases of RA (). Again, these patients were followed up by a mixed group of providers (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Another study carried out in the province of Pisa in the years 2006 and 2007 14 evaluated the prevalence of RA, the reliability of the RA diagnosis and prevalence estimated by general practitioners (GPs), and the economic impact of the disease in a total of 26,709 subjects aged over 18 years. Each GP completed a questionnaire on their patients; patients considered by GPs to have RA were then invited to attend an appointment at a specialist rheumatology center for confirmation or rejection of the diagnosis made.…”
Section: Methodsmentioning
confidence: 99%
“…In a health economic analysis carried out in the province of Pisa in the years 2006 and 2007, 14 the mean annual cost per patient with RA was estimated to be €5,878 (median €6,434; interquartile range €669–€7,052), with high variability, mainly depending on the degree of disability. In this analysis, more than 90% of the overall annual cost per patient was due to the medical and nonmedical components of direct costs.…”
Section: Methodsmentioning
confidence: 99%